Penerapan Narasi Ekspositoris dalam Penulisan Naskah Video Dokumenter “Jejak yang Tersulam di Balik Motif Batik Rumah Gajah Mungkur” - Windy Nur Octaliya; Priyo Subekti; Gumgum Gumilar (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2026)
Batik is an Indonesian cultural heritage recognized by UNESCO as an Intangible Cultural Heritage of Humanity on 2 October 2009. One local batik rich in historical and philosophical value yet lacking audio-visual documentation is Batik Gajah Mungkur from Gresik, East Java, particularly the Rumah Gajah Mungkur motif, an exclusive design not owned by any other batik producer in Gresik. This final project aims to analyze the creative process of the documentary video "Jejak Yang Tersulam Di Balik Motif Batik Rumah Gajah Mungkur" from pre-production to post-production, and to describe the application of expository narrative in its scriptwriting. The creation process involved in-depth research, field observation, and interviews with three sources: the owner of Batik Gajah Mungkur, a batik consumer, and the Deputy Chair of the Surabaya Indonesian Batik Lovers Community (KCBI). The script was structured into three acts, namely introduction, content, and closing, with voice over narration serving as the connecting thread integrating visuals, interviews, and background music. The result shows that the expository narrative was applied by arranging the historical and philosophical information in a gradual and coherent manner. This documentary is expected to serve as a digital cultural archive and educational medium in preserving Batik Gajah Mungkur as part of Gresik's cultural identity.